2011
DOI: 10.1088/0256-307x/28/8/087306
|View full text |Cite
|
Sign up to set email alerts
|

Dipolar and Quadrupolar Modes of SiO 2 /Au Nanoshell Enhanced Light Trapping in Thin Film Solar Cells

Abstract: Dipolar and quadrupolar resonance wavelengths of SiO2/Au nanoshell surface plasmons are designed at 560 nm to enhance the light trapping in thin film solar cells. In order to quantitatively describe the light trapping effect, the forward-scattering efficiency (FSE) and the light trapping efficiency (LTE) are proposed by considering the light scattering direction of SiO2/Au nanoshells. Based on the Mie theory, the FSE and the LTE are calculated for SiO2/Au nanoshells of different dimensions, and the contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…So, quickly forming enough minority carriers in the channel in the inversion regime is indispensable to correctly measure the minority carrier-related program/erase speed in a memory capacitor structure. In order to enhance the minority carrier generation rate in a memory capacitor, illumination [9,10] is employed during the P/E transient measurement. Figure 2 presents a scheme to measure erase transient characteristics for a p-channel memory capacitor under illumination.…”
Section: Effect Of Slow Minority Carrier Generation Time In Memory Ca...mentioning
confidence: 99%
“…So, quickly forming enough minority carriers in the channel in the inversion regime is indispensable to correctly measure the minority carrier-related program/erase speed in a memory capacitor structure. In order to enhance the minority carrier generation rate in a memory capacitor, illumination [9,10] is employed during the P/E transient measurement. Figure 2 presents a scheme to measure erase transient characteristics for a p-channel memory capacitor under illumination.…”
Section: Effect Of Slow Minority Carrier Generation Time In Memory Ca...mentioning
confidence: 99%
“…1,2 Among various metal nano array structures, the spherical shell structure has attracted more attention because of its relatively simple preparation and wide tuning range of LSPR wavelength. [3][4][5][6][7] It is shown that the LSPR resonance peak can be changed by varying the shape, size, spacing and surrounding environment of the nanoparticles on the liquid, silicon or glass substrates. [8][9][10][11][12] In recent years, considerable progress has been made in the preparation and application of metal nanospheres.…”
Section: Introductionmentioning
confidence: 99%
“…This greatly enhanced EM field, known as surface plasmon resonance (SPR), has received wide applications such as to surface enhanced spectra, [3,4] sensors, [5] thermal imaging and therapy, [6] plasmonic lasers, [7] ultra transmission, [8,9] abnormal reflection, [10] photocatalysis [11] and solar energy. [12,13] Considering the SPR has a strong relationship to the geometry of structures and wavelength of the incident light, the enhancement of the EM field has been studied in the past all over the world on various plasmonic structures, such as nanoparticles, [14] nanowires, [15] nanorods, [9,16] nanoholes, [17] nanodisks, [18] and closed nanorings. [19] In the near-infrared, those nanostructures are used in plasmonic devices for optical communications, [20] thermal imaging, [21−23] biomedical application, [6,24] solar energy, [13,25] etc.…”
mentioning
confidence: 99%
“…[12,13] Considering the SPR has a strong relationship to the geometry of structures and wavelength of the incident light, the enhancement of the EM field has been studied in the past all over the world on various plasmonic structures, such as nanoparticles, [14] nanowires, [15] nanorods, [9,16] nanoholes, [17] nanodisks, [18] and closed nanorings. [19] In the near-infrared, those nanostructures are used in plasmonic devices for optical communications, [20] thermal imaging, [21−23] biomedical application, [6,24] solar energy, [13,25] etc. In addition to the abovementioned nanostructures, the split nanorings have been suggested as interesting plasmonic nanostructures for making sensors, [26] lasing spacers and coherent plasmon emitters in the near-infrared region.…”
mentioning
confidence: 99%